(untitled) (Interdisciplinary Studies Journal, 2025)
This article analyzes the effectiveness of Article 20 of the Brazilian General Data Protection Law (LGPD) as a legal mechanism to protect voters against algorithmic manipulation in electoral contexts. The research is justified by the increasing sophistication of digital technologies, which are reshaping the political environment and threatening citizens’ informational autonomy. The general objective is to assess whether this legal provision is sufficient to protect voters’ subjectivity and agency in the digital age. The specific objectives include: (i) contextualizing the phenomenon of algorithmic manipulation; (ii) examining the normative content of Article 20 and its limitations; (iii) discussing emblematic practical cases; and (iv) proposing pathways to strengthen democratic governance. The methodology adopted is qualitative, based on an interdisciplinary literature review in the fields of Law, Philosophy of Information, and Political Science, complemented by an analysis of normative documents and national and international case studies. Drawing on Luciano Floridi’s concepts of “infosphere” and “onlife,” it is demonstrated that digital manipulation operates as an active vector of democratic risk. It is concluded that an approach focused solely on the individual is insufficient; instead, a public governance model oriented toward systemic risks is required to preserve the integrity of democracy in the algorithmic age.